KUALITATIF SISTEM PELAPORAN REKAM MEDIS ELEKTRONIK (RME) RAWAT INAP DI RSUD dr. MOHAMMAD ZYN KABUPATEN SAMPANG: Qualitative Electronic Medical Record Reporting System (RME) Inpatient at dr. Mohammad Zyn Sampang Regency - Prisusanti, Retno Dewi; Nabila, Gadisania Versya; Dhiba, Shafrina Fara (Forind Press, 2024)
This study examines the challenges and solutions in the implementation of the inpatient electronic medical record (RME) system at dr. Mohammad Zyn Hospital, Sampang Regency. Through qualitative methods involving in-depth interviews with doctors, nurses, and administrative staff, it was found that lack of training, inadequate technological infrastructure, and resistance to change were the main obstacles. However, the potential benefits of RME in improving the efficiency and quality of health services are significant. Proposed solutions include increased training and education, investment in technology infrastructure, effective change management, and regular monitoring and evaluation of the RME system. This study emphasizes the importance of collaboration between hospital management, medical staff, and stakeholders to optimize the implementation of RME and improve the quality of health services in hospitals.